1987
DOI: 10.1111/j.1748-1716.1987.tb08187.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of Lipoxin A include lung strip contraction and dilation of arterioles in wiwo

Abstract: Lipoxin A ([5S,6R,15S]-5,6,15-trihydroxy-7,9,13-trans-11-cis-eicosatetraenoic acid), a recently characterized lipoxygenation product of arachidonic acid, in submicromolar concentrations elicited long-lasting contractions of the guinea-pig lung strip. The response to lipoxin A was not due to release of acetylcholine, histamine, noradrenaline or cyclo-oxygenase products. 15-hydroperoxyeicosatetraenoic acid (15-HPETE), one precursor of lipoxin A, also contracted the lung strip, but 15-HPETE was less potent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…For example, at submicromolar concentrations, lipoxins stimulate endothelial-dependent relaxation of aortic strips (41). LXA4 also provokes vasodilation (in vivo) (42)(43)(44) and stimulates the formation of prostacyclin by human endothelial cells, albeit at higher concentrations (45). In addition to extracellular roles, LXA4 may also serve an intracellular function since it activates isolated protein kinase C (46) and selectively stimulates its 'y-subspecies (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, at submicromolar concentrations, lipoxins stimulate endothelial-dependent relaxation of aortic strips (41). LXA4 also provokes vasodilation (in vivo) (42)(43)(44) and stimulates the formation of prostacyclin by human endothelial cells, albeit at higher concentrations (45). In addition to extracellular roles, LXA4 may also serve an intracellular function since it activates isolated protein kinase C (46) and selectively stimulates its 'y-subspecies (47).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they suggest that lipoxins can also be formed after initial oxygenation by the 5-LO and transcellular metabolism. Since lipoxins have been found to possess vasoactive functions (41)(42)(43)(44)(45), their formation during the interaction of PMNs with platelets may have implications in the regulation of hemostasis, inflammation, and the interactions of these cells with the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is the recruitment and activation of neutrophils, through the 15-lipoxygenase pathway, by airway epithelial cells [43][44][45][46][47]. Another system implicated in airway inflammatory responses, which could be triggered by the alteration of the epithelial surface, is the sensory nerves.…”
Section: Airway Epithelial Damagementioning
confidence: 99%
“…More recently, LxA4 has been shown to contract pulmonary smooth muscle (i.e., guinea pig lung) and to relax vascular smooth muscle (8) at concentrations <1 ,uM. Dahlen et al (8) further showed that LxA4 had no significant myotropic activity on either guinea pig trachea or guinea pig ileum (8).…”
mentioning
confidence: 98%